Peran Bidan dalam Memberikan Promosi Kesehatan Terhadap Sadari pada Remaja Putri tentang Sadari Di UPT. Puskesmas Sigumpar - Dwi Pratiwi Kasmara (UNIVERSITAS ADIWANGSA JAMBI, 2023)
Normal breasts number in a pair and are always located on the chest - there is an abnormality when there are additional breasts that are not located on the chest but in other parts of the body, for example the armpits. Breast cancer is a type of cancer that attacks the breast organs, where cells in the breast divide and grow out of control. This cancer is one of the most common types of cancer suffered by people, especially women. Early Detection of Breast Cancer, can be done with BSE (Breast Self-Examination). Midwives are at the forefront who accompany women of all ages, midwives have access to educate women to do BSE. The research design used is analytic. This type of research uses a cross sectional approach. The population of this study were all young women aged 16-19 with the age range in the UPT area. Sigumpar Health Center, Kec. Sigumpar consisted of 35 young women. The sampling technique used in this study was total sampling. From the results of the statistical analysis of the chi-square test, the p-value = 0.005 was obtained. Statistically, it can be concluded that Ha is accepted, meaning that there is a relationship between the midwife's role in providing health promotion to adolescents about BSE at UPT. Sigumpar Health Center, Kec. Sigumpar. It is recommended that midwives provide more creative, interesting and innovative promotions.